LINGUISTIC FEATURES OF COFFEE ADVERTISING SLOGANS IN ENGLISH AND VIETNAMESE / Phan Thị Mai Hương; Supervisor: Le Phuong Thao Dr - Phan, Thị Mai Hương
This study focused on syntactic and semantic features of coffee advertising slogans in English and Vietnamese to find out the similarities and differences between them. This research used quantitative and qualitative approaches. A quantitative approach was employed to obtain the frequency of the types of structures, and the types of meaning conveyed through the selected slogans. And the qualitative approach was used to describe and analyze the features of slogans from linguistic aspects. The data were in the form of slogans used by different companies in English and Vietnamese. The results of this research show that in terms of syntax, clauses, phrases, and simple sentences are the most common structures used in English slogans, while Vietnamese ones focus on clauses and sentences. These structures in general keep the slogans short, and easy to remember, which are the key points in making marketing and creating slogans. In terms of meanings, both English and Vietnamese slogans convey different types of meaning to make a specific impression, but most of them express the conceptual meaning which shows the direct meaning based on the dictionary. These results are meaningful for those who are working in marketing, for lecturers who are teaching language, and for learners who are studying English language, so that they can have different viewpoints about the language used in advertising language in general, and in slogan in specific.